0342 Early Morning Alpha Amylase Activity and Insomnia: Exploring the Transition from Acute Insomnia to Recovery, Persistent Poor Sleep, or Chronic Insomnia. (27th April 2018) - Muench, A L; Vargas, I; Gencarelli, A; Khader, W; Boyle, J T; Ellis, J; Perlis, M L
Abstract: Introduction: Insomnia is widely conceptualized as a disorder of hyperarousal (cortical, cognitive, & somatic). Somatic markers of hyperarousal are, however, understudied. For example, the association between insomnia and salivary alpha amylase (sAA), a biomarker for sympathetic nervous system activation, has yet to be formally investigated. In the present study, morning sAA activity was assessed in a sample of good sleepers (GS) and subjects who transitioned from Acute Insomnia (AI) to Recovery (REC), persistent poor sleep (PPS), or chronic insomnia (CI). Methods: The study included data from 20 adults (mean age = 58.8 years; 75% female) recruited from a larger, longitudinal study (n = 1, 069). This sub-sample participated in two overnight lab-based studies, that occurred over two consecutive nights, approximately 3-months apart. Five subjects per group were chosen based on their clinical status at Time 1 (GS or AI) and were classified based on status at Time 2 (GS, REC, PPS or CI). Six saliva samples were collected in total, one at bedtime and five the subsequent morning (once every 15 minutes from lights on). Results: At T1, subjects with CI had tended to have lower sAA activity at bedtime (means [SD]: CI=51.1[32.3]; PPS=136.1[173.1]; REC=141.0[157.2]; GS=129.3[152.1]) and at awakening (means: CI=24.9[26.3]; PPS=104.9[92.3]; REC=134.0[101.5]; GS=132.0[124.0]) and significantly blunted post-awakening sAA deactivation slope as compared to the other three groups (results from linear mixed models; group x time, F = 12.3, p < 0.001). Data at Time 2 showed similar associations but all effects were ns. Conclusion: According to several models of insomnia, hyperarousal is a core feature of the disorder. The present findings, however, suggest that sympathetic activation [at bedtime and in the early morning] is lower among individuals with CI. This said, closer temporal analysis may reveal that there are transient increases in sAA associated with AI that resolve with time. Support (If Any): Perlis: NIH R01AG041783 & Ellis: Economic and Social Research Council (RES-061-25-0120-A).